Using Decision Analysis to Provide Integrated, Transparent Trade‐off Analysis. Issue 4 (8th January 2019) - Specking, Eric
ABSTRACT: Clients often ask systems engineers to communicate the complexities of their studies or to review/understand someone else's study. Exploring, evaluating, and communicating the tradespace is difficult to do, especially when reviewing others' work, due to the lack of knowledge of the tradespace, number and types of models, the complexities of the analysis, and the adequacy of the documentation. Additionally, it is challenging to identify and demonstrate important trade‐offs found throughout the design decision process. This demonstrates a need to understand the complexities of the analysis, be able to visualize their relationships, and then be able to communicate it to others in a simplified manner that technical and non‐technical stakeholders can understand. This article describes: (1) how system engineering requires descriptive, predictive, and prescriptive analytics in early system design, (2) a framework for an integrated trade‐off analytics approach that incorporates the various analytics categories with model‐based engineering and model‐based system engineering, and (3) a decision analysis tool called the trade‐off analytics hierarchy that transparently identifies and communicates the complexities of an analysis to stakeholders.